P117 Effects of transcranial direct current stimulation on the functional coupling of the sensorimotor cortical network. Issue 3 (March 2017) - Di Iorio, R.; Vecchio, F.; Pellicciari, M.C.; Miraglia, F.; Brignani, D.; Granata, G.; Miniussi, C.; Rossini, P.M.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) is well establishedamong the non-invasive brain stimulation techniques as a method to modulate brain excitability. Polarity-dependent modulations of membrane potentials are detected after the application of anodal and cathodal stimulation, leading to changes in the electrical activity of the neurons. Objective: The main aim of the present study was to test the hypothesis that tDCS can affect in a polarityspecific manner the functional coupling of the sensorimotor areas during the eyes-open resting condition as revealed by total EEG coherence (i.e., coherence across the average of all combinations of the electrode pairs placed around the stimulation electrode). Material & methods: The changes in the total EEG coherence were evaluated pre-, during, and post-anodal and cathodal tDCS. Results: While no differences were observed in the connectivity characteristics of the two pre-stimulation periods, a connectivity increase was observed in the alpha 2 band in the post-anodal tDCS with respect to pre-anodal and post-cathodal tDCS. Conclusions: The present study suggests that a specific approach based on the analyses of the functional coupling of EEG rhythms might enhance understanding of tDCS-induced effects on cortical connectivity. Moreover, this result suggests that anodal tDCS could possibly modify cortical connectivity more effectively with respect to cathodal tDCS.